2008
DOI: 10.3390/s8116791
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical DNA Biosensor Developed on a Nanocomposite Platform of Gold and Poly(propyleneimine) Dendrimer

Abstract: An electrochemical DNA nanobiosensor was prepared by immobilization of a 20mer thiolated probe DNA on electro-deposited generation 4 (G4) poly(propyleneimine) dendrimer (PPI) doped with gold nanoparticles (AuNP) as platform, on a glassy carbon electrode (GCE). Field emission scanning electron microscopy results confirmed the co-deposition of PPI (which was linked to the carbon electrode surface by C-N covalent bonds) and AuNP ca 60 nm. Voltammetric interrogations showed that the platform (GCE/PPI-AuNP) was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…Electrodes are modified to enhance response or selectivity towards a particular substrate. Materials such as redox polymers [6,7], dendrimers [8], nanoparticles [9,10] are commonly used to prepare modified electrodes. In the analysis of dopamine in particular, gold nano film [11] carbon electrode modified with polyglycine [1], poly(acid chrome blue K) [2] and others [1,12,13] have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodes are modified to enhance response or selectivity towards a particular substrate. Materials such as redox polymers [6,7], dendrimers [8], nanoparticles [9,10] are commonly used to prepare modified electrodes. In the analysis of dopamine in particular, gold nano film [11] carbon electrode modified with polyglycine [1], poly(acid chrome blue K) [2] and others [1,12,13] have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…R s models the solution resistance, R 1 and R 2 represent the resistance to the flow of the perchlorate ion through the polymer. where the constant phase element (CPE) with an a value of between 0.8 and 0.87 was used in place of capacitance for better fitting [17]. On the bare Pt electrode, lithium perchlorate showed a two time constant behavior as seen in the two / max of the phase angle in Fig.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Dendrimers, with their easily accessible multiple terminal or end functional group, are ideal for the construction of star-shaped polymers [15]. Electrochemistry and sensor application of pristine PPI, metallo-PPI and PPI-gold nanocomposites have been studied by our group [16][17][18]. The nanoscale structures of dendrimers have a variety of other applications in the fields of coatings, chemical sensors catalytic nanoreactors, drug delivery systems and liquid crystalline dendrimers [19].…”
Section: Introductionmentioning
confidence: 99%
“…The detection limit was 3.5 x 10 -14 M [54]. 20-mer thiolated probe DNA immobilized on electrodeposited poly(propyleneimine) doped with gold nanoparticles on glassy carbon electrode was prepared Arotiba et al The nanosensor responded to target DNA in a dynamic linear range of 0.01-5 nM using [Fe(CN) 6 ] 3-/4-redox probe [55]. A DNA hybridization biosensor based on ssDNA/cytochrome c/L-cysteine/gold nanoparticles/chitosan monolayer modified on glassy carbon electrode by Li et al The amount of adsorbed DNA was found as 1.672 x 10 -10 mol/cm 2 based on DPV response of daunomycin indicator [8].…”
Section: Studies Based On Both Nanoparticles and Polymersmentioning
confidence: 99%